Facebook Marketplace Utilization Training to Support Digital Entrepreneurship in Generation Z - Ibnu Phonna Nurdin; Dara Fatia; Khalisni Khalisni; Riki Yulianda; Teuku Muhammad Husni; Asnika Putri Simanjuntak; Mutiara Fitri; Syafira Aulia Rangganis; Bella Billiant J Ananta Kembaren; Rianti Putri (Dedikasi Sosial: Jurnal Pengabdian Masyarakat, 2026)
The development of digital technology has encouraged an increase in entrepreneurial activities among Generation Z by utilizing various e-commerce platforms that are currently widely circulated among the public. However, the use of Facebook's Marketplace is still relatively low compared to other platforms. Even though the Facebook marketplace platform has various advantages, such as no administration fees, transparent bargaining, product transparency, a Cash on Delivery (COD) payment system, and making it easier to reach the local market, this condition shows that efforts are needed so that Generation Z understands the potential of the Facebook Marketplace in supporting digital entrepreneurship. This service activity aims to improve the understanding and skills of Generation Z in utilizing the Facebook Marketplace application as an alternative medium for buying and selling transactions in today's digital age. The method of implementing activities includes: preparation, socialization, training, and practice assistance, as well as evaluation and non-continuation of activities. The number of participants involved in this activity was 20 participants from Generation Z who lived in the city of Banda Aceh. The results of the activity showed that participants were able to understand the various benefits and advantages of using the Facebook Marketplace. Not only that, but participants were also able to quickly operate the Facebook Marketplace application independently and quickly learn about the series of product sales in the application. The evaluation of this activity showed that the participants were very enthusiastic about using this application to support their work as traders. Thus, this service activity has been carried out on target in increasing digital literacy to Generation Z. It is hoped that this understanding can also be passed on to other Generation Z in various regions in Indonesia as a form of supporting economic sustainability in the younger generation.